A simple measuring set-up for the experimental determination of the dynamics of a large particle in the 3D velocity field around a free surface vortex. (March 2019) - Duinmeijer, Simon P.A.; Moreno-Rodenas, Antonio M.; Lepot, Mathieu; van Nieuwenhuizen, Christian; Meyer, Irene; Clemens, François H.L.R.
Abstract: Vortices are a very common phenomenon to consider in many hydraulic engineering problems, e.g. when designing pump sumps or intake works for turbines. Until now, the focus is on avoiding the development of vortices because of induction of cavitation and air entrainment by a fully developed air core. However, vortices may also be used in a more positive manner e.g. by taking advantage of the capacity to transport (floating) particles to avoid the built up of scum layers in wastewater pump sumps. To the authors' knowledge only little literature is available in this specific field of research. In order to obtain state-of-the art data on the dynamics of large particles in a free-surface vortex flow field and to examine the vortex transport capacity, a simple but novel 3D-PTV (Particle Tracking Velocimetry) method using 6 iPhones was designed, built, tested and employed to measure the 3D-motion of a large particle in the vortex flow. The experimental set-up, particle detection method and the post-processing of the raw data are described in detail along with some first experimental results. The presented 3D-PTV method showed to be able to obtain data that can be used for detailed analysis of the dynamics of large particles in the vortex flow. The overall standard uncertainty of the particle centre position is in the order of magnitude of 0.1 mm in each direction in a volume of a diameter of 0.6 m and a height of about 1 m, while recording at 240 fps. Highlights: The experimental set-up is built from 'of the shelf components'. The behaviour of relatively large particles (relative to the vortex core diameter) is monitored. The experimental set-up is described in great detail.